2019
DOI: 10.32327/ijmess/8.2.2019.8
|View full text |Cite
|
Sign up to set email alerts
|

Remittance and Economic Growth Nexus in Nigeria: Does Financial Sector Development Play a Critical Role?

Abstract: The purpose of the study was to examine the relationship between remittances, financial sector development, and economic growth in Nigeria over the period 1981 to 2017. The study used the autoregressive distributed lag (ARDL) model to analyze the longrun and short-run relationships between the variables. The outcome of the study revealed that the variables are bound together in the long-run. The results also showed that remittances have a negative and significant effect on economic growth both in the long-run … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
7
20
2
Order By: Relevance
“…This negative relationship was also established in the short run. This finding is in line with Anetor (2019), although contrary to findings by Afaha (2013) and Meyer and Shera (2017). The negative relationship between remittances and economic growth simply implies that a large inflow of remittances does not necessarily lead to economic growth.…”
Section: Human Capital Flight and Output Growthsupporting
confidence: 48%
See 1 more Smart Citation
“…This negative relationship was also established in the short run. This finding is in line with Anetor (2019), although contrary to findings by Afaha (2013) and Meyer and Shera (2017). The negative relationship between remittances and economic growth simply implies that a large inflow of remittances does not necessarily lead to economic growth.…”
Section: Human Capital Flight and Output Growthsupporting
confidence: 48%
“…Again, Nigeria is one of the many countries experiencing a high rate of human capital flight and understanding the impact of this on output growth, in the long run, is a welcome development. Furthermore, the reviews have shown that many studies carried out in Nigeria either examined the factors that contributed to migration (Ndulu, 2010;Joshua et al, 2014;Egbefo, 2014;Tabassum et al, 2017;Ajide and Alimi, 2018;Popogbe and Adeosun, 2020) or examined the impact of remittances on the Human capital flight and output growth home economies (Anetor, 2019;Mago, 2018;Azizi, 2018). On another hand, while the studies by Henry (2013) and Okonkwo et al (2020) on the impact of capital flight on economic growth in Nigeria have a semblance of our current study; however, it is important to note that human capital flight and capital flight are two distinct concepts.…”
Section: Human Capital Flight and Output Growthmentioning
confidence: 99%
“…Remittance's role in the financial system has been extensively investigated through divers measures, such as financial inclusion (Aggarwal et al, 2006 ; Chowdhury, 2011 ; Anetor, 2019 ; Sobiech, 2019 ) and financial innovation. Despite the increasing value of remittances, little research has been done on the relationship between remittances and financial access.…”
Section: Literature Review: Remittance Openness and Financial Stabilitymentioning
confidence: 99%
“…Literature review Anetor (2019) examine the relationship between remittances, financial sector development, and economic growth in Nigeria over the period 1981 to 2017. The author used the autoregressive distributed lag (ARDL) model to analyze the long-run and short-run relationships between the variables.…”
Section: Introductionmentioning
confidence: 99%